Motives for Active Participation in Political Blogs: A Qualitative and Quantitative Analysis of Eight German Blogs. (April 2014) - Greuling, Kathrin; Kilian, Thomas
Blogs play an important role in political communication and in forming the opinions of political actors and politically interested users. Their ability to facilitate active interaction, present opinions, mobilize voters, and thereby, influence public opinion and eventually election outcomes makes political blogs an interesting research subject. Thus, this article draws upon a qualitative content analysis to reveal the readers' motivations and main themes to post comments and get involved in the discussions on political blogs. We analyze 12 blog discussions (500 pages) in eight left-leaning German political blogs and use qualitative content analysis to develop a category scheme comprising of 3, 868 codings. We find that social interaction with other blog users is the main motive for blogging on German political blogs together with the desire for the exchange of further information and analysis, and the expression of the own opinion concerning the subject. Moreover, we classify 191 users by their motivations for blogging using cluster analysis and identify the bloggers' different communication roles. By providing insight into the users' political discussions, motives for participation, and communication roles, we clarify the role that political blogs play in the process of forming political opinion and derive implications for politics.